(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article explores the role of family upbringing in developing children’s ethnocultural competence. It examines key methods of ethnocultural education in the family, including teaching and using the native language, reading and discussing national literature. Participation in cultural traditions, celebrating national holidays, preserving ethnocultural customs, and engaging in community activities are analyzed as ways to help children understand and respect their ethnic and cultural roots. Additionally, methods for gaining ethnocultural experience within the family, teaching children about parental history and traditions, and maintaining and transmitting religious values are presented, which contribute to the spiritual, moral, and social development of the child. The aim of this article is to provide practical recommendations for fostering ethnocultural competence in children through family upbringing and to create conditions for their social, cultural, and spiritual growth by preserving local traditions and religious values.